1977
DOI: 10.1213/00000539-197709000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Control of Gastric Acidity by Glycopyrrolate Premedication in the Parturient

Abstract: The effect of premedication with the anticholinergic quaternary ammonium compound, glycopyrrolate (0.4 mg), on gastric juice pH was investigated in 23 parturients scheduled for elective cesarean section under general anesthesia, and the results were compared to a control group of 15 nonpremedicated obstetric patients and 25 parturients premedicated with atropine (0.6 mg). In the nonpremedicated control group, the mean gastric juice pH was 2.36 (SE +/- 0.23), 66% having a pH less than the critical level of 2.5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The most often used opiate-anticholinergic combination, morphine-scopolamine, has been shown to significantly increase gastric fluid pH with no adverse effect on volume when compared to a benzodiazepine ( 16). The anticholinergic drug, glycopyrrol-ate, used in 12% of departments as premedication before C-section, significantly reduces gastric acid production (5), and may therefore also be considered as AAS prophylaxis ( 12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most often used opiate-anticholinergic combination, morphine-scopolamine, has been shown to significantly increase gastric fluid pH with no adverse effect on volume when compared to a benzodiazepine ( 16). The anticholinergic drug, glycopyrrol-ate, used in 12% of departments as premedication before C-section, significantly reduces gastric acid production (5), and may therefore also be considered as AAS prophylaxis ( 12).…”
Section: Resultsmentioning
confidence: 99%
“…Acid Aspiration Syndrome (AAS) is a well-known complication of general anaesthesia in gynaecological and obstetric patients (1)(2). Numerous studies (4)(5)(6)(7)(8)(9)(10) have dealt with preoperative fasting and chemoprophylaxis in these patients. Surveys ( 1 1-14) have shown marked differences in AAS prophylaxis between countries.…”
mentioning
confidence: 99%
“…Various methods of increasing the pH of gastric contents before the induction of anaesthesia have been tried (Taylor and Pryse-Davis, 1966;Crawford, 1971;Salem et al, 1976;Baraka et al, 1977;Hester and Heath, 1977). Anticholinergic drugs inhibit the production of gastric juice, but to a variable degree.…”
mentioning
confidence: 99%
“…However, the 26 per cent (8 of 31) incidence of gastric residue pH lower than 2.5 in patients who received cimetidine compares favourably with some other reported groups of patients undergoing elective Caesarean section. In a study which considered three such groups, Baraka (1977) found that the incidence of gastric fluid pH lower than 2.5 at induction of anaesthesia was 66 per cent (10 of 15) in patients who received no premedication or prophylaxis, 60 per cent (15 of 25) in those who received premedication with atropine 0 . 6 mg and 35 per cent (8 of 23) in those who received premedication with glycopyrrolate 0 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently attempts have also been made to reduce the acidity of gastric contents by reducing gastric acid secretion as opposed to neutralisation with antacids. Premedication before elective Caesarean section with the anticholin-ergic quaternary ammonium compound glycopyrrolate was reported to reduce the incidence of gastric fluid pH of lower than 2.5 to 34 per cent compared with an incidence of 66 per cent in unpremedicated controls (Baraka et al, 1977). In patients undergoing elective gynaecological surgery, a single oral dose of cimetidine 400 mg was shown to be highly effective in raising the pH of gastric fluid above 2.5 (Husemeyer et al, 1978).…”
Section: Prophylaxis For Mendelson's Syndrome Before Elective Caesarementioning
confidence: 99%